Teaching English vowels to Spanish speakers. - Gallardo del Puerto, Francisco; Gómez Lacabex, Esther (Pulso. Revista de educación, 2008)
This paper focuses on the teaching of English vowels to Spanish students. The introduction discusses the importance of addressing pronunciation in the foreign language classroom in order to achieve a native or intelligible accent, it emphasizes the relevance of the first language sound system when acquiring the pronunciation of a second language, and it reviews the role of the teacher in pronunciation teaching. The second part presents a comparative study of English and Spanish vowel systems, which helps to understand the differences and similarities between the two languages and, consequently, many of the phenomena found in the pronunciation of English vowels by Spanish speakers. The last section includes a series of didactic and pedagogic resources for the formal instruction of English pronunciation, with special reference to the teaching of vowels.